A mobile phone text-based intervention to enhance HIV/AIDS risk reduction among long-distance truckers in Kenya: Development and validation using an e-Delphi technique - Cyrus Mutie; Kawira Kithuci; John Gachohi; Grace Mbuthia (Digital Health)
Objective The study aimed to develop and validate messages for a mobile phone text-based intervention to enhance human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) risk reduction among long-distance truckers (LDTs) in Kenya. Methods and methodology Initially, key facts and updates on HIV/AIDS risk reduction were extracted from existing guidelines and packaged into short messages targeted for LDTs. Subsequently, a panel of interdisciplinary experts was purposively sampled and invited through individual emails to participate in the e-Delphi exercise. The study involved three phases: formative research, intervention development, and content validation. Two rounds of the e-Delphi exercise were conducted. A consensus threshold of above 75% was adopted. A Fleiss’ kappa ( K ) statistic was computed to assess the interrater reliability levels in each round of the e-Delphi exercise. Results Most experts were of Kenyan citizenship, 21 (88%), except for one Ugandan and two South Africans. A total of 56 items were rated by 24 experts in round one. Out of the 56 items rated in round one, 50 achieved a consensus above 75%. Based on feedback from specific experts in round one, six items were amended, and an extra one was formulated. In round two, seven items were rated. The seven items achieved a consensus level of 98.21%, meaning a third round was unnecessary. Conclusion Given the multi-dimensional inputs from the interdisciplinary panel of experts, the text-based intervention is considered a valid tool for promoting HIV/AIDS risk reduction among LDTs. Considering the substantive approval of the intervention from the panel of experts, a short message service-based digital delivery platform will be used in the implementation phase. We recommend regular updates of the intervention, as the evidence is expected to grow and evolve further.